Cardiac telocytes were decreased during myocardial infarction and their therapeutic effects for ischaemic heart in rat. Issue 1 (4th December 2012) - Zhao, Baoyin; Chen, Shang; Liu, Juanjuan; Yuan, Ziqiang; Qi, Xufeng; Qin, Junwen; Zheng, Xin; Shen, Xiaotao; Yu, Yanhong; Qnin, Thomas J.; Chan, John Yeuk‐Hon; Cai, Dongqing
Abstract Recently, cardiac telocytes were found in the myocardium. However, the functional role of cardiac telocytes and possible changes in the cardiac telocyte population during myocardial infarction in the myocardium are not known. In this study, the role of the recently identified cardiac telocytes in myocardial infarction (MI) was investigated. Cardiac telocytes were distributed longitudinally and within the cross network of the myocardium, which was impaired during MI. Cardiac telocytes in the infarction zone were undetectable from approximately 4 days to 4 weeks after an experimental coronary occlusion was used to induce MI. Although cardiac telocytes in the non‐ischaemic area of the ischaemic heart experienced cell death, the cell density increased approximately 2 weeks after experimental coronary occlusion. The cell density was then maintained at a level similar to that observed 1–4 days after left anterior descending coronary artery (LAD)‐ligation, but was still lower than normal after 2 weeks. We also found that simultaneous transplantation of cardiac telocytes in the infarcted and border zones of the heart decreased the infarction size and improved myocardial function. These data indicate that cardiac telocytes, their secreted factors and microvesicles, and the microenvironment may be structurally and functionally important for maintenance of the physiological integrity of the myocardium. Rebuilding the cardiac telocyte network in the infarcted zone following MI may be beneficial for functional regeneration of the infarcted myocardium.